Cytokines’ gene expression, humoral immune and biochemical responses of common carp (Cyprinus carpio, Linnaeus, 1758) to transportation density and recovery in brackish water - Seyyed Morteza Hoseini (2019)
© 2019 Elsevier B.V. The aim of the present study was to investigate the effects of stocking density during transportation and post-transportation salt treatment on stress, hydromineral, immunological and antioxidant responses in common carp (Cyprinus carpio). For this, the fish were transported in plastic bags for 4 h at two densities: 100 (LD) and 200 (HD) g/L and allowed to recover for 24 h in both freshwater (FW) and brackish water (3 g/L sodium chloride; BW). Water physicochemical parameters were determined after transportation. Blood stress, immunological and hydromineral responses, head kidney cytokine gene expression, and liver antioxidant responses were determined. The transportation led to significant decrease in water dissolved oxygen and pH, and increase in water total and unionized ammonia levels. Water dissolved oxygen was significantly lower, whereas, water total and unionized ammonia were significantly higher in the HD, compared to the LD group. Serum cortisol and glucose, and liver malondialdehyde levels, and expression of tumor necrosis factor-alpha, interleukin-1beta and interleukin-8 genes increased after transportation. Serum ion levels and liver superoxide dismutase and catalase decreased after transportation. All the above-mentioned changes, except for cortisol and catalase, were more severe in the HD compared to the LD group. There were no significant changes in serum total immunoglobulin and alternative complement after transportation, compared to before transportation values; but the LD group had significantly higher alternative complement than the HD group. Lysozyme and WBC significantly increase in the LD group; whereas, significantly decreased in the HD group, after transportation. Recovery in BW was useful to mitigate stress response, hydromineral imbalance, immunosuppression and oxidative stress caused by the transportation. Using sodium chloride is recommended during fish recovery from transportation, particularly when the fish are transported at high stocking density. The benefits of sodium chloride treatment seem to be mediated by restoration of hydromineral balance and oxidative status, which leads to healthier fish with higher immune responses.